2022
DOI: 10.3390/ijerph19042261
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Levels and Screen Time among Youth with Overweight/Obesity Using Mental Health Services

Abstract: Youth with mental illness have higher levels of obesity than children in the general population. Both regular physical activity and limited screen time have been recommended to reduce and prevent childhood obesity. This study examines accelerometer-based moderate–vigorous physical activity (MVPA) and screen time among youth with overweight/obesity issues who are receiving mental health care. This study looked at a 12-month weight management randomized clinical trial for overweight/obese youth aged 8–18 years w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Consequently, only meeting sleep recommendations is not considered a sufficient strategy for reducing obesity [48]. The existing literature provides further evidence supporting the association between being overweight and experiencing poorer health-related quality of life (HQOL), as well as reduced levels of physical literacy components [51], such as physical activity practice and sedentary behavior [52,53]. Additionally, studies have shown that the inverse relationship between sleep duration and adiposity in adolescents also impacts HQOL and physical literacy [51].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, only meeting sleep recommendations is not considered a sufficient strategy for reducing obesity [48]. The existing literature provides further evidence supporting the association between being overweight and experiencing poorer health-related quality of life (HQOL), as well as reduced levels of physical literacy components [51], such as physical activity practice and sedentary behavior [52,53]. Additionally, studies have shown that the inverse relationship between sleep duration and adiposity in adolescents also impacts HQOL and physical literacy [51].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, only meeting sleep recommendations is not considered a su cient strategy for reducing obesity (46). The existing literature provides further evidence supporting the association between being overweight and experiencing poorer health-related quality of life (HQOL), as well as reduced levels of physical literacy components (49), such as physical activity practice and sedentary behavior (50,51). Additionally, studies have shown that the inverse relationship between sleep duration and adiposity in adolescents also impacts HQOL and physical literacy (52).…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity plays a very important role in prevention, as well as treatment of obesity ( 37 ). Physical activity should be adapted according to age and comorbidities ( 38 ). For example, the use of a pedometer has been associated with increased physical activity in adult patients, as well as a decrease in BMI.…”
Section: Non-pharmacological Therapymentioning
confidence: 99%